Central stars of planetary nebulae: II. New OB-type and emission-line stars - Weidmann, Walter Alfredo (2011)
There are more than 3000 confirmed and probably known Galactic planetary nebulae (PNe), but central star spectroscopic information is available for only 13% of them. Aims. We have undertaken a spectroscopic survey of the central stars in PNe to identify their spectral types. Methods. We performed spectroscopic observations at low resolution with the 2-m telescope at CASLEO, Argentina. Results. We present the spectra of 46 central stars of PNe, most of them are OB-type and emission-line stars.